Seed quality differences in diverse seed colored Indian mustard (Brassica juncea) genotypes - Yadav, Sangita; Yadav, Shiv K; Swami, Sunil; Saini, NAVINDER; Hussain, Zakir; Vasudev, Sujata; Yadava, D K (The Indian Journal of Agricultural Sciences, 2020)
‘Canola quality’ Indian mustard (Brassica juncea) with varying seed color are a new kind of breeding resources with single zero genotypes having low level of erucic acid (